Invisible - Gonzalez, Christian Diaz, ....-; Epstein, Gabriela, ....- (New York : Scholastic, 2022)
Can five overlooked kids make one big difference? There's George: the brain, Sara: the loner, Dayara: the tough kid, Nico: the rich kid, and Miguel: the athlete. And they're stuck together when they're forced to complete their school's community service hours. Although they're sure they have nothing in common with one another, some people see them as all the same... just five Spanish-speaking kids. Then they meet someone who truly needs their help, and they must decide whether they are each willing to expose their own secrets to help... or if remaining invisible is the only way to survive middle school.
Keywords: Graphic novel; Vriendschap